Analysis of the Thymidylate Synthase Gene Structure in Colorectal Cancer Patients and Its Possible Relation with the 5-Fluorouracil Drug Response - Calascibetta, A.; Contino, Flavia; Feo, S.; Gulotta, G.; Cajozzo, M.; Antona, A.; Sanguedolce, G.; Sanguedolce, R. (Journal of Nucleic Acids, 2010)
Thymidylate synthase (TS) catalyzes methylation of dUMP to dTMP and it is the target for the 5-Fluorouracil (5-FU) activity. Barbour et al. showed that variant structural forms of TS in tumour cell lines confer resistance to fluoropyrimidines. We planned to perform the whole TS gene structure by means of sequencing techniques in human colorectal cancer (CRC) samples to try to identify the presence of any possible TS variant form that could be responsible of fluoropyrimidines drug resistance and of the worse prognosis. We performed the TS-DNA gene sequence in 68 CRC from patients of A, B, and C Dukes' stages and different histological grade, but we did not find any mutation in the TS-DNA structure. In the future we intend to widen the TS structure analysis to the metastatic CRCs, because due to their higher genomic instability, they could present a TS variant form responsible of the fluoropyrimidines drug resistance and the worse prognosis.